2001
DOI: 10.1037/h0087123
|View full text |Cite
|
Sign up to set email alerts
|

A review of programs to promote family wellness and prevent the maltreatment of children.

Abstract: Les changements annuels de la motivation envers les math6matiques au secondaire selon rage et le sexe des 616ves

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 75 publications
1
18
0
2
Order By: Relevance
“…Present findings agree with the general literature on gender differences and also with the general gender differences in beliefs, which suggest that both children and their families are prone to perceive gender differences. They also corroborated previous research either in the area of health-related quality of life or in the area of developmental psychology (Caldera & Hart, 2004;Harding, 2001;Kazdin & Whitley, 2003;Matos et al, 2006;Nelson et al, 2001). The fact that parents are not totally aware of their children's subjective health-related quality of life perceptions and that parents perceive a difference according to the gender and the age of their children has implications for intervention with families of school-aged children.…”
Section: Discussionsupporting
confidence: 73%
“…Present findings agree with the general literature on gender differences and also with the general gender differences in beliefs, which suggest that both children and their families are prone to perceive gender differences. They also corroborated previous research either in the area of health-related quality of life or in the area of developmental psychology (Caldera & Hart, 2004;Harding, 2001;Kazdin & Whitley, 2003;Matos et al, 2006;Nelson et al, 2001). The fact that parents are not totally aware of their children's subjective health-related quality of life perceptions and that parents perceive a difference according to the gender and the age of their children has implications for intervention with families of school-aged children.…”
Section: Discussionsupporting
confidence: 73%
“…Offering services early on can help a family first recognize the problem and second, provide their own insights into a solution. Nelson, Laurendeau, and Chamberland (2001) have also found that families who are in crisis situations are in need of a wide variety of supports that are usually only available through government interventions. These include adequate and affordable child care, health care, and housing (Gaudin, 1993).…”
Section: Intervention/preventionmentioning
confidence: 99%
“…L'équipe du projet a procédé à la diffusion des résultats de l'étude en utilisant différentes modalités : a) des publications scientifiques (Nelson, Laurendeau et Chamberland, 2001 ;Prilleltensky, Nelson et Peirson, 2001 ;Prilleltensky et Nelson, 2000) ; b) une trousse vulgarisée offrant un résumé des principales conclusions de l'étude (Prilleltensky et al, 1999) 2 ; c) un rapport de la consultation menée à travers le Canada (Peirson et al, 1998).…”
Section: This Paper Reports On the Results Of The Quebec Component Ofunclassified